Analisis Karakteristik Pasang Surut Air Laut terhadap Elevasi pada Pelabuhan Perairan Tanjung Uncang - Indrastuti Indrastuti; Nelso Chen (Jurnal Ilmiah Rekayasa Sipil, 2022)
The tidal wave of seawater is one of the critical factors in port planning related to determining elevation. This research aimed to assess the effect of a tidal wave in the planning of port elevation at the Port of Tanjung Uncang so that the ship's estimated time can be determined. The research method is quantitatively based on primary data from PT. Graha Trisaka Industri and field observations. The results showed that the types of tides at Tanjung Uncang port were mixed tides, prevailing semi diurnal, which experienced two high tides and two low tides in one day. The highest sea level elevation (HHWS) occurred at 354.8 cm (+166.2 cm from MSL) and the lowest low sea level elevation occurred at -20 cm (-186.2 cm from MSL).